Drug addiction as a cause of diminished responsibility: A study from the principle of shared responsibility - Vaca Espinosa, Jorge Rafael; Carvajal Renza, Boris (DIXI, 2026)
The phenomenon of drug use has traditionally been associated with primary criminalization, namely, the creation of criminal offenses. However, in recent decades this issue has been addressed in light of the constitutional framework, which has guided judicial decisions aimed at curbing the criminalization of consumers and recognizing that, in contexts of social exclusion, addicted individuals may be entitled to a reduction of sentence. This study seeks to analyze the different dogmatic approaches through which this social problem can be addressed in relation to criminal conduct, from the perspective of the principle of State co-responsibility. A qualitative methodology with a legal focus is employed, grounded in the review of judicial rulings, specialized doctrine, and the principles of the Social Rule of Law. This analysis paves the way to propose, de lege ferenda, the recognition of diminished imputability accompanied by security measures directed at the treatment of addiction in Colombia.